Potential role of comprehensive dental care in preventing medication related osteonecrosis of the jaw (MRONJ): a single centre study - Kamila Alblazi; Syed Nabil; Nor Rafeah Tumian; Siti Salmiah Mohd Yunus; Roszalina Ramli (BMC, 2024)
Abstract Objective Medication-related osteonecrosis of the jaw bones (MRONJ) is a well-known complication of antiresorptive and antiangiogenic drugs. Since the first report, more occurrences of MRONJ have been described worldwide. Dental extraction has been described by many studies as one of the risk factors for MRONJ. Comprehensive dental care (CDC) is a preventive dental method provided to patients prior to drug commencement. This study aims to determine the association between CDC and MRONJ. Patients and methods. A retrospective analysis was performed on 75 medical records of patients on antiresorptive and/or antiangiogenic drugs between February 2018 and May 2021. Demographics and clinical and radiographic data were collected. Univariate and multivariate analyses were performed to determine the factors associated with MRONJ. Results Of the 75 patients who met the inclusion criteria, 11 (14.7%) developed MRONJ. Three out of 11 patients (27.2%) developed MRONJ spontaneously, while eight patients (72.8%) developed it after trauma from dentures or dental extractions. Following a binary logistic regression analysis, the lack of CDC was identified as a significant predictor of MRONJ. Patients who did not receive CDC had an odds ratio of 8.64 (95% confidence interval (CI): 1.27-58.62, p = 0.03). However, dental extraction did not show a statistically significant association with MRONJ in both the univariate and multivariate analyses. Conclusion CDC before treatment with antiresorptive and antiangiogenic drugs is a potentially effective preventive method for reducing MRONJ. Dental extraction was not a significant factor in relation to MRONJ.